2008
DOI: 10.1111/j.1742-7843.2008.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Preventive Effect of Nicorandil on Ischaemia‐Induced Ventricular Tachyarrhythmia in Isolated Arterially Perfused Canine Left Ventricular Wedges

Abstract: Whether nicorandil is effective at preventing ventricular tachyarrhythmia (VT) during acute myocardial ischaemia is still controversial. We examined effects of nicorandil on the induction of VT during acute myocardial ischaemia. Optical action potentials were recorded from the entire transmural wall of arterially perfused canine left ventricular wedges. Ischaemia was produced by arterial occlusion for 20 min. During endocardial pacing, nicorandil shortened mean action potential duration (APD) in the transmural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…HMR1098 also abolished the protective effect of nicorandil on the conduction failure. In contrast to atria, HMR1098 had no effect on nicorandil-induced attenuation of ischemic conduction slowing in ventricle [9]. These results suggest that the mechanisms of nicorandil-induced protection against ischemic conduction disturbances in atria are different from those in ventricle.…”
Section: Mechanisms For the Protective Effects Of Nicorandil On Ischecontrasting
confidence: 69%
See 4 more Smart Citations
“…HMR1098 also abolished the protective effect of nicorandil on the conduction failure. In contrast to atria, HMR1098 had no effect on nicorandil-induced attenuation of ischemic conduction slowing in ventricle [9]. These results suggest that the mechanisms of nicorandil-induced protection against ischemic conduction disturbances in atria are different from those in ventricle.…”
Section: Mechanisms For the Protective Effects Of Nicorandil On Ischecontrasting
confidence: 69%
“…However, a recent study has demonstrated the different structure of atrial and ventricular sarcolemmal K ATP channels in mice [15]: a sulfonylurea receptor 1 (SUR1) is an essential component of atrial but not ventricular K ATP channels, although SUR2A was expressed in both atrium and ventricle. Our studies demonstrated that nicorandil dosedependently shortened APD in the left ventricle [9] but not in the left atrium before ischemia, suggesting the differences in structure of sarcolemmal K ATP channels between atrium and ventricle in canine. Nevertheless, our results suggest the same mechanism of nicorandilinduced ischemic APD shortening between atria and ventricles.…”
Section: Mechanisms For the Protective Effects Of Nicorandil On Ischementioning
confidence: 71%
See 3 more Smart Citations